Home » Past Questions » Mathematics » If b = a + cp and r = ab + \(\frac{1}{2}\)cp2, express b2 in terms of a, c, r....

If b = a + cp and r = ab + \(\frac{1}{2}\)cp2, express b2 in terms of a, c, r....


Question

If b = a + cp and r = ab + \(\frac{1}{2}\)cp2, express b2 in terms of a, c, r.

Options

A) b2 = aV + 2cr

B) b2 = ar + 2c2r

C) b2 = a2 = \(\frac{1}{2}\) cr2

D) b2 = \(\frac{1}{2}\)ar2 + c

E) b2 = 2cr - a2

The correct answer is E.

Explanation:

b = a + cp....(i)
r = ab + \(\frac{1}{2}\)cp2.....(ii)
expressing b2 in terms of a, c, r, we shall first eliminate p which should not appear in our answer from eqn, (i)
b - a = cp = \(\frac{b - a}{c}\)
sub. for p in eqn.(ii)
r = ab + \(\frac{1}{2}\)c\(\frac{(b - a)^2}{\frac{ab + b^2 - 2ab + a^2}{2c}}\)
2cr = 2ab + b2 - 2ab + a2
b2 = 2cr - a2

More Past Questions:


Dicussion (1)

  • b = a + cp....(i)
    r = ab + \(\frac{1}{2}\)cp2.....(ii)
    expressing b2 in terms of a, c, r, we shall first eliminate p which should not appear in our answer from eqn, (i)
    b - a = cp = \(\frac{b - a}{c}\)
    sub. for p in eqn.(ii)
    r = ab + \(\frac{1}{2}\)c\(\frac{(b - a)^2}{\frac{ab + b^2 - 2ab + a^2}{2c}}\)
    2cr = 2ab + b2 - 2ab + a2
    b2 = 2cr - a2

    Reply
    Like